Phosphorus uptake and rhizosphere properties of alfalfa in response to phosphorus fertilizer types in sandy soil and saline-alkali soil - Zhang, Tianchan; Wan, Weifan; Sun, Zhi; Li, Haigang (Frontiers in Plant Science, 2024)
Introduction Phosphorus (P) fertilizer is critical to maintain a high yield and quality of alfalfa (Medicago sativa L.). There are several fertilizer types and soil types in China, and the application of a single type of P fertilizer may not be suitable for present-day alfalfa production. Methods In order to select the optimal combination of alfalfa and soil type and fertilizer type for improving P utilization efficiency. We conducted a greenhouse pot experiment, calcium superphosphate (SSP), diammonium phosphate (DAP), ammonium polyphosphate (APP), potassium dihydrogen phosphate (KP), and no-fertilizer control treatments were applied to alfalfa in sandy and saline-alkali soils. The response of alfalfa root morphology and rhizosphere processes to different P fertilizers was investigated. Results and discussion The results showed that shoot biomass of alfalfa was slightly higher in sandy soil than in saline–alkali soil. Shoot biomass of alfalfa increased by 223%-354% in sandy soil under P treatments compared with the control, and total root length increased significantly by 74% and 53% in DAP and SSP treatments, respectively. In saline–alkali soil, alfalfa shoot biomass was significantly increased by 229% and 275% in KP and DAP treatments, and total root length was increased by 109% only in DAP treatment. Net P uptake of alfalfa in DAP treatment was the highest in both soils, which were 0.73 and 0.54 mg plant-1, respectively. Alfalfa shoot P concentration was significantly positively correlated with shoot and root biomass (P < 0.05, 0.01 or 0.001) whereas negatively correlated with acid phosphatase concentration (P < 0.05). Improvement of plant growth and P uptake induced by P fertilizer application was greater in sandy soil than in saline–alkali soil. DAP and KP was the most efficient P fertilizers in both sandy soil and saline–alkali soil.